Designing the Visual Identity of Kabba Tourism Village, Minasatene District: Maximizing Culinary Potential and the Natural Beauty of Karst - Tamsil, Kevin; Korel, Adeline Y.; Tenggrana, Edison Jaya; Adelia; Tjandinegara, Owen Matthew; Nugraha, Ahmad Ade (Jurnal Strategi Desain dan Inovasi Sosial, 2025)
This study focuses on designing the visual identity of Kabba Tourism Village, Minasatene District, Pangkajene and Kepulauan Regency, South Sulawesi, Indonesia. to maximize its culinary potential and the natural beauty of its karst formations. A tourism village is a concept where a village leverages its natural, cultural, and culinary wealth to attract tourists. Kabba Village has significant potential in the tourism sector with its unique karst formations and ponds. However, the village faces challenges, including the lack of a distinct visual identity. Kabba Village was ranked in the top 300 of the Anugerah Desa Wisata Indonesia (ADWI) in 2023, indicating its considerable potential. Nevertheless, the village has not yet fully utilized these advantages, particularly in terms of a visual identity that can attract tourists. This study aims to design a visual identity inspired by the natural beauty and culinary richness of Kabba Village, such as its unique karst formations, fish and shrimp products, and the traditional craftsmanship of baka-baka. The research employs the Research and Development (R&D) method with a design thinking approach. Qualitative data were collected using observation, interviews, and secondary data analysis, while the visual identity design was developed through the stages of empathy, reframing, ideation, prototyping, and testing. The results of this study are expected to serve as a reference for the further development of Kabba Village as a tourism village, or to provide insights for the development of other tourism villages in Indonesia. A strong visual identity is anticipated to enhance Kabba Village’s appeal as a competitive tourism destination in South Sulawesi.